The 2020 UV emitter roadmap - Amano, Hiroshi; Collazo, Ramón; Santi, Carlo De; Einfeldt, Sven; Funato, Mitsuru; Glaab, Johannes; Hagedorn, Sylvia; Hirano, Akira; Hirayama, Hideki; Ishii, Ryota; Kashima, Yukio; Kawakami, Yoichi; et al. (Journal of physics. D, Applied physics, 2020)
Solid state UV emitters have many advantages over conventional UV sources. The (Al,In,Ga)N material system is best suited to produce LEDs and laser diodes from 400 nm down to 210 nm-due to its large and tuneable direct band gap, n- and p-doping capability up to the largest bandgap material AlN and a growth and fabrication technology compatible with the current visible InGaN-based LED production. However AlGaN based UV-emitters still suffer from numerous challenges compared to their visible counterparts that become most obvious by consideration of their light output power, operation voltage and long term stability. Most of these challenges are related to the large bandgap of the materials. However, the development since the first realization of UV electroluminescence in the 1970s shows that an improvement in understanding and technology allows the performance of UV emitters to be pushed far beyond the current state. One example is the very recent realization of edge emitting laser diodes emitting in the UVC at 271.8 nm and in the UVB spectral range at 298 nm. This roadmap summarizes the current state of the art for the most important aspects of UV emitters, their challenges and provides an outlook for future developments.